Epidermal and Melanocitic Tumors in Dogs and Cats: a Review - Daria Antonia DUMITRAȘ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine, 2019)
Skin is the organ-barrier which assures the isolation and the protection of the organism, but in the same time, it is vulnerable because of its continuous exposure to various environmental factors. Unfortunately, the prevalence of skin cancer in pet animals continues to rise. Several studies have been conducted with the purpose of establishing incidence rates of skin cancer in pets, revealing that regarding dogs, tumors of the skin are the most common, accounting for approximately 30% of all tumors. Similarly, skin tumors in cats are very often diagnosed, accounting for approximately 25% of all tumors (Meuten, 2012; Withrow and Vail, 2007). Considering the importance of deepening the studies related to skin cancer in dogs and cats, this review aims to emphasize the most common types of epidermal and melanocytic neoplastic lesions, highlighting their prevalence, the associated factors, the gross morphology and the histological features.